Blasting pressure for LiNi1/3Mn1/3Co1/3O2 battery evaluated by thermally adiabatic testing - Wang, Yih-Wen; Huang, Hsiao-Ling (Journal of thermal analysis and calorimetry, 2021)
Gas evolution that resulted in the pressure elevation on LiNi 1/3 Mn 1/3 Co 1/3 O 2 (NMC111) battery in case of a runaway reaction was discussed with the thermally explosive behaviors. The NMC111 cell and 2 series-connected (2S) NMC111 module both with 100% SoCs (state of charges) were examined the pressure rise rates in an open-circuit voltage (OCV) state using VSP2 adiabatic calorimetry. The charged NMC111 module underwent an extremely runaway reaction at elevated temperatures and caused a thermal explosion due to high potential energy inside the battery and interaction with the cell components. The surface temperature of the cell during the charge-discharge cycle was measured to compare with the difference in heat accumulation at 0.75, 1, 2 C-rates. Furthermore, the blasting pressure that propagated a thermal explosion for both single cell and 2S module were evaluated. The significant explosion potential increased with the electric potential. Moreover, the considerable quantities of gases eruption from the full-charged batteries can result in battery rupture and flames from a confined battery housing.